2002
DOI: 10.1152/ajplung.00216.2001
|View full text |Cite
|
Sign up to set email alerts
|

Killing ofKlebsiella pneumoniaeby human alveolar macrophages

Abstract: We investigated putative mechanisms by which human surfactant protein A (SP-A) effects killing of Klebsiella pneumoniae by human alveolar macrophages (AMs) isolated from bronchoalveolar lavagates of patients with transplanted lungs. Coincubation of AMs with human SP-A (25 microg/ml) and Klebsiella resulted in a 68% decrease in total colony forming units by 120 min compared with AMs infected with Klebsiella in the absence of SP-A, and this SP-A-mediated effect was abolished by preincubation with N(G)-monomethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 56 publications
2
50
0
1
Order By: Relevance
“…Klebsiella administration (42). Other investigators have likewise established the essential role that alveolar macrophages play in clearing bacterial pathogens from the lung via their phagocytic and bactericidal functions (43)(44)(45)(46)(47). In this study, we demonstrate yet another potentially important function of alveolar macrophages in innate immunity: as an early source of IFN-␥.…”
Section: Discussionsupporting
confidence: 59%
“…Klebsiella administration (42). Other investigators have likewise established the essential role that alveolar macrophages play in clearing bacterial pathogens from the lung via their phagocytic and bactericidal functions (43)(44)(45)(46)(47). In this study, we demonstrate yet another potentially important function of alveolar macrophages in innate immunity: as an early source of IFN-␥.…”
Section: Discussionsupporting
confidence: 59%
“…AMs comprise the first line of host defense against microorganisms, but their potency in killing K. pneumoniae remains incompletely understood (25). Our data showed that internalization (phagocytosis) into AMs was significantly decreased by MbCD pretreatment ( Figure 4B), indicating that cholesterol-containing membrane microdomains may be related to the phagocytosis of this pathogen.…”
Section: Raft-dependent Bacterial Internalization Is Enhanced By Delementioning
confidence: 77%
“…The intracellular killing of K. pneumoniae is likely mediated by several microbicidal molecules, including antimicrobial peptides, reactive nitrogen intermediates, and ROIs (21,(38)(39)(40)(41). However the individual contributions of such molecules are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo treatments of mice with the nitric oxide synthase inhibitor, L-NAME, impaired host defense against K. pneumoniae (41). Interestingly, HickmanDavis and colleagues (40) demonstrated (in a cell-free system) that, although neither ROIs nor nitric oxide alone were toxic to K. pneumoniae, potent bacterial killing could be observed when a combination of nitric oxide and superoxide was present (at a pH of 5.0), suggesting that optimal bactericidal activity can be achieved when peroxynitrite is formed in an acidic milieu. Our data support this result, as we find requirements for both nitric oxide and NADPHox activation in macrophage killing of K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%